Stanisław Judycki: The Seriousness and Courage of Philosophy - Pyda, Janusz (Roczniki Filozoficzne, 2024)
In this text I present the philosophical profile of Stanislaw Judycki. Referring to the conception of philosophy outlined in Prof. Judycki’s text entitled “Why is philosophy difficult?” I try to show how the author of this conception remained faithful to it in his original philosophical work. Thus, I try to bring out and discuss the most important features of Stanislaw Judycki’s way of doing philosophy as well as the characteristic features of the philosophy that resulted from it. I also discuss in summary form some of the most important themes and problems taken up by Stanislaw Judycki and the characteristic features of his philosophical writing.